2012
DOI: 10.1182/blood-2012-03-414755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of refractory/relapsed myeloid leukemia in children with Down syndrome

Abstract: Myeloid leukemia in Down syndrome (ML-DS) is associated with good response to chemotherapy and favorable prognosis. Because little research has been focused on refractory/relapsed (R/R) cases, we conducted a retrospective analysis for R/R ML-DS. Among ML-DS patients diagnosed between 2000 and 2010 in Japan, 26 relapsed (25 in the BM and 1 in the skin), and 3 refractory patients were enrolled. The male/female ratio was 18/11. The median age at initial diagnosis of ML-DS was 2 years, and the median time to relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 19 publications
1
55
2
Order By: Relevance
“…17,18 Of 6 patients who received SCT, 4 are alive and 2 died. Thus, new therapies such as histone deacetylase inhibitors and Wee1 inhibitors need to be developed for patients with refractory or relapsed ML-DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Of 6 patients who received SCT, 4 are alive and 2 died. Thus, new therapies such as histone deacetylase inhibitors and Wee1 inhibitors need to be developed for patients with refractory or relapsed ML-DS.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] ML-DS patients with either refractory or relapsed disease have a very poor prognosis even after receiving stem cell transplants (SCTs). [16][17][18] Hence, identifying the optimal treatment intensity for ML-DS patients remains a challenge, balancing the need to use curative therapy while minimizing treatment-associated morbidity and mortality. The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…19 In summary, we show that therapy reduction could be achieved in children with ML-DS without compromising the excellent outcome. The identification of clinical and cytogenetic prognostic markers in our study offers new possibilities for risk-adapted therapy for children with ML-DS.…”
Section: Aml-bfm 98 Ml-dsmentioning
confidence: 99%
“…14,15 In contrast, the prognosis of relapsed ML-DS patients is extremely poor. 12,19,20 This means that ML-DS treatment schemata have to particularly strive for the balance between appropriate chemotherapy dosage to avoid relapses and treatment-related toxicity. Despite substantial efforts, clear prognostic factors that identify those patients at high risk for relapse remain elusive precluding a risk-adapted treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,32 ML-DS AMKL cases are characterized by mutations in the hematopoietic transcription factor GATA1, and these patients have a good prognosis when treated with reduced-intensity chemotherapy because of the unique sensitivity of leukemia cells to chemotherapeutic agents. 21,22,[32][33][34][35][36] Our group previously showed that RBM15/MKL1, CBFA2T3/GLIS2, NUP98/ KDM5A, and KMT2A rearrangements were not present in ML-DS. 5 GATA1 mutations have been described in non-Down syndrome AMKL, often seen with an acquired trisomy 21, and it was suggested that these cases fare well in terms of prognosis, although numbers were small.…”
mentioning
confidence: 94%